2008
DOI: 10.2307/25470709
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress in the Intertidal: Comparing Survival and Growth of an Invasive and Native Mussel Under a Variety of Thermal Conditions

Abstract: In the rocky intertidal, organisms frequently experience a wide range of daily body temperatures depending on the stage of the tide and the time of day. In the intertidal, the thermal adaption of a species and its ability to invade a new region may be closely linked. In this research, the physiological effects of thermal stress in both low tide and high tide conditions are compared between Mytilus galloprovincialis, a worldwide mussel invader, and M. trossulus, a sibling species. In a seawater tank, mussels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 57 publications
2
54
0
1
Order By: Relevance
“…smaller effect sizes) and enjoyed higher survival following elevated body temperature than did M. trossulus, in accord with our expectations based on a number of other studies (Braby and Somero, 2006b;Lockwood et al, 2010;Lockwood and Somero, 2011;Schneider, 2008;Schneider and Helmuth, 2007;Tomanek and Zuzow, 2010). These data add to the growing literature demonstrating that, among mussel species, disparate combinations of physiology and behavior play a crucial role in ecological success of species, notably in the context of biological invasions (de Zwaan et al, 1991;Lockwood and Somero, 2011;Nicastro et al, 2010;Schneider et al, 2005;Shinen and Morgan, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…smaller effect sizes) and enjoyed higher survival following elevated body temperature than did M. trossulus, in accord with our expectations based on a number of other studies (Braby and Somero, 2006b;Lockwood et al, 2010;Lockwood and Somero, 2011;Schneider, 2008;Schneider and Helmuth, 2007;Tomanek and Zuzow, 2010). These data add to the growing literature demonstrating that, among mussel species, disparate combinations of physiology and behavior play a crucial role in ecological success of species, notably in the context of biological invasions (de Zwaan et al, 1991;Lockwood and Somero, 2011;Nicastro et al, 2010;Schneider et al, 2005;Shinen and Morgan, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…4; supplementary material Table S2). This fits with a growing body of research showing that invasive species are often more thermally tolerant than related noninvasive species (Schneider, 2008;Sorte et al, 2010a;Lenz et al, 2011;Lockwood and Somero, 2011;Zerebecki and Sorte, 2011). A recent meta-analysis concluded that, in aquatic environments, invasive species performed significantly better at increased temperatures than did co-occurring native species (Sorte et al, 2013).…”
Section: Discussion Eurythermalitysupporting
confidence: 79%
“…Based on their natural distribution, the Eastern Pacific M. trossulus seem to prefer colder temperatures and tolerate lower salinity levels, whereas the Mediterranean M. galloprovincialis is a warm-water species that prefers high salinity levels (Seed, 1992). Measurements of growth, heart rate and survival generally confirm these interspecific differences (Braby and Somero, 2006b;Schneider, 2008). One hypothesis for the underlying mechanistic differences is that M. trossulus may achieve tolerance to lower salinities by closing their shells, as indicated by a drop in heart rate (Braby and Somero, 2006b).…”
Section: Introductionmentioning
confidence: 66%